Implementation of Cooperative Learning in Islamic Religious Education Teaching - Anati Rahila (STIT Attaqwa, 2025)
This study is intended to find out how the implementation of cooperative learning methods in Islamic religious education learning. This research uses qualitative methods sourced from literature studies in the form of previous research, journals, newspapers, magazines and books that discuss similar research. The result of this study is that the cooperative learning method has a significant effect on learning Islamic religious education. Cooperative learning as a learning method that emphasizes cooperation and interaction between students can increase cooperation and good interaction skills. This method can be implemented through group work and discussion in learning Islamic religious education so that it is more interesting and interactive.